Kritik Islamic Worldview Syed Muhammad Naquib Al-Attas terhadap Western Worldview - Hasan, Nur (MarÃƒÂ¢ji`: Jurnal Ilmu Keislaman, 2014)
This article would like to review more about how the Western worldview is according to Syed Muhammad Naquib al-Attas and how his Islamic worldview critique is to the Western worldview. Islamic worldview, according to him, is a view of life that is born from the concepts in Islam. Al-Attas in his critique states that the Islamic worldview appeared concurrently with the presence of Western worldview, where this worldview holds only the empirical orientation. Western worldview based on secular ideology that separates between worldly and religious affairs. For al-Attas, Islam has an authentic worldview. With the authentic worldview, he blocked all attempts to westernization by using the term dewesternization. Dewesternization tries to eliminate the influences of the West against the East (Islam).